Height velocity and its relation with serum ferritin and pretransfusion haemoglobin in thalassemia patients: results from a tertiary center in Northeast India - Mahanta, Bikashita; Nath, Ananta Kumar; Biswanath, Pranabjit (International Journal of Contemporary Pediatrics, 2022)
Background: ẞ-thalassemia syndromes are the commonest single gene disorders in the Indian population and growth failure remains a major concern among these patients. Methods: We studied the relation of height velocity with serum ferritin and pretransfusion hemoglobin in 30 transfusion dependent thalassemia patients aged 1-12 years attending our centre. The height measurements were taken every 6 months for one year. Serum ferritin was measured 3 monthly and pretransfusion hemoglobin was measured at each visit. Results: The prevalence of impaired height velocity in transfusion dependent thalassemics in our study was 56.67%. The mean pretransfusion hemoglobin was 7.8±1.065 g/dl and the mean serum ferritin level in our study was 2426±872 ng/ml. In thalassemia patients with height velocity < 3rd percentile mean serum ferritin level was 2637±892.84 ng/ml while the mean serum ferritin level in patients with height velocity >3rd percentile was 1875±564.007 ng/ml with a statistically significant relation (p=0.012). Although the mean pretransfusion hemoglobin in children with height velocity <3rd percentile was found to be lower compared to their counterparts with height velocity >3rd percentile (7.42±0.879 g/dl vs. 7.96±0.998 g/dl), this relation was found to be statistically insignificant (p value=0.127). Conclusions: Our study highlights that even though regular blood transfusions are essential in thalassemic patients, maintaining an optimal ferritin level is equally essential in influencing growth in these children.